2008
DOI: 10.1007/s12098-008-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Gap between awareness and practices regarding maternal and child health among women in an urban slum community

Abstract: Wide gaps exist between awareness and practices related with MCH due to non-adoption of knowledge into actual practice, except some selected components lacking in both knowledge as well as practice. Need for bridging the existing gaps avoiding socio-cultural barriers and misconceptions prevailing in the community and by promoting and protecting healthy MCH care practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 3 publications
3
16
0
Order By: Relevance
“…Their level of knowledge regarding communicable diseases, infections, child nutrition, personal hygiene is crucial to their corresponding practices which will have direct or indirect impact on their child's health 9 . Various studies which were done to study the knowledge among mothers regarding the use of ORS in diarrhea have reported that maternal literacy had a significant influence on the practice of ORS in diarrhea [10][11][12] .Literature from various studies reveals that even though the mothers have a good knowledge about diarrhea and ORS but the attitude and practices during the disease are inappropriate 13,14,15,16 . Diarrhea is a both preventable and treatable disease, but due to improper knowledge of mothers and their misdirected approach towards the disease management results into severe dehydration and death 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Their level of knowledge regarding communicable diseases, infections, child nutrition, personal hygiene is crucial to their corresponding practices which will have direct or indirect impact on their child's health 9 . Various studies which were done to study the knowledge among mothers regarding the use of ORS in diarrhea have reported that maternal literacy had a significant influence on the practice of ORS in diarrhea [10][11][12] .Literature from various studies reveals that even though the mothers have a good knowledge about diarrhea and ORS but the attitude and practices during the disease are inappropriate 13,14,15,16 . Diarrhea is a both preventable and treatable disease, but due to improper knowledge of mothers and their misdirected approach towards the disease management results into severe dehydration and death 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of these patients turned up in paediatrician clinics rather than to the paediatric surgeons, hence the diagnostic delays in paediatric achalasia are usually due to misinterpretation of these typical findings. [18][19][20] We had higher pulmonary symptoms (73.9%) than Eckards' series (33%). [10] The probable cause of higher pulmonary infection was faulty feeding practices by illiterate parents in the developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The probable cause of higher pulmonary infection was faulty feeding practices by illiterate parents in the developing countries. [20] The manometery remains the diagnostic modality of choice for achalasia (highest sensitivity), but we lack the facility even at tertiary referral centre, because of inequality of health resources in India. [21][22][23] If we further refer these patients to higher centres (few in developing countries), where these facilities are available, a long waiting list at these centres, assessability and affordability of parents' further delays the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cent per cent respondents also disagreed with the item as "pregnant mother should do more laborious work". Kumar et al, (2008) found thatlow levels of awareness and practice of TT immunization (74.2% awareness, 58.1% practice), five-cleans (31.9% awareness and 14.4% practice), trained birth attendant (69.6% awareness 39.1% practice), and postnatal care (75.4% awareness and 51.0% practice) among lactating mothers. Knowledge regarding optimal infant and young child feeding practices was very poor: initiation of breast-feeding within six hours (17.4%), colostrum feeding (34.8%), exclusive breastfeeding (5.8%) and significant gaps between knowledge and practice were observed.…”
Section: Health For Pregnant and Lactating Mothermentioning
confidence: 97%